Semen quality and frozen semen production in Pasundan bulls: A molecular weight perspective on seminal plasma and spermatozoa protein - Baharun, Abdullah; Rahmi, Annisa; Handarini, Ristika; Maulana, Tulus; Said, Syahruddin; Iskandar, Hikmayani; Darussalam, Imam; Nalley, Wilmientje Marlene Mesang; Arifiantini, Raden Iis (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: To determine the correlation between the molecular weight (MW) of proteins in seminal plasma and spermatozoa and the quality of fresh and frozen semen production in Pasundan bulls. Materials and methods: Nine selected Pasundan bulls, aged 5–10 years, from the Regional Artificial Insemination Center at Ciamis, West Java, Indonesia, were used in the study, with fresh semen sperm motility ≥70% and <70%. We analyzed the motility, viability, integrity of the intact plasma membrane (IPM), and the morphological characteristics of spermatozoa. 1D-SDS-PAGE analysis was performed to determine the protein profile by assessing MW, depicted as bands on the gel. Results: The motility, viability, and IPM of spermatozoa had lower values (p < 0.05) in Pasundan bulls named Bagaskara and Kertarajasa compared to the other bulls. Proteins with MW 35–50 kDa were not detected in the seminal plasma of Pasundan bulls, exhibiting low quality in fresh semen. The correlation analysis showed that the non-detected proteins with MW 35–50 kDa in seminal plasma correlated with spermatozoa motility (r = 0.421), viability (r = 0.424), and IPM (r = 0.428) so that fresh semen quality was low in both Pasundan bulls. Analysis of semen volume, spermatozoa concentration, and spermatozoa motility showed that the average frozen semen production of Pasundan bulls per ejaculate was 128.73 ± 15.35 straws. Conclusion: Protein analysis based on MW is a predictive indicator for the quality of fresh semen and the production of frozen semen in Pasundan bulls. Evaluation parameters of fresh semen quality by MW analysis can be used to select Pasundan bulls in Indonesia. J. Adv. Vet. Anim. Res., 10(4): 730–737, December 2023 http://doi.org/10.5455/javar.2023.j728